The isolation and characterization of coagulasenegative Staphylococcus sp. from intestine of a Malaysian rabbit (Oryctolagus cuniculus) - Tengku Abdul Hamid, Tengku Haziyamin; Mazlan, Farhaneen Afzal (Faculty of Resource Science and Technology, Universiti Malaysia Sarawak, 2012)

(untitled)
The isolation and characterization of lactic acid bacteria (LAB) from the intestine of Oryctolagus cuniculus, a domestic rabbit species in Malaysia is described. Fifty isolates from rabbit intestine were screened by biochemical tests. From 50 isolates, four were identified and shown to be catalase-positive, lactose positive and Gram-positive cocci. Antibacterial assays were carried out against Escherichia coli and Salmonella enteritidis as indicator bacteria. The samples exhibited antibacterial properties as indicated by zone of inhibitions. Three isolates were further subjected to 16S ribosomal RNA (rRNA) gene sequencing and analysis. Partial 16SrRNA sequencing results from these isolates showed high sequence similarity with coagulase negative Staphylococcus sp. This result showed that by screening of LAB from rabbit intestine, bacteria from the family Staphylococcaceae could be isolated and this could be potentially used as probiotics in rabbit feeding.